Characterization of TEMPO‐oxidized cellulose nanofibers in aqueous suspension by small‐angle X‐ray scattering. (1st April 2014) - Su, Ying; Burger, Christian; Hsiao, Benjamin S.; Chu, Benjamin
<x xml:space="preserve">Abstract</x> Cellulose nanofibers, extracted from wood pulps using the (2, 2, 6, 6‐tetramethylpiperidine‐1‐yl)oxyl (TEMPO)‐mediated oxidation method, are low‐cost, sustainable and high‐performance materials with potential usage in many applications. The structural information of these cellulose nanofibers in aqueous suspension was characterized by synchrotron small‐angle X‐ray scattering (SAXS). A simplified ribbon model having a near rectangular cross section was found to give the best fit to the SAXS results. The analytical expression of the ribbon model also led to a higher calculation efficiency compared with the more conventional parallelepiped model. The extracted structural information included the cross‐section size and size distribution of the cellulose nanofibers. For example, for nanofibers prepared from the dried pulp of the maritime pine, the size‐weighted averages of thickness and width were 3.2 and 12.7 nm, respectively, and the corresponding standard deviations were 2.2 and 5.5 nm, respectively. The scattering results of the size‐weighted average of the nanofiber width are also consistent with those determined directly from transmission electron microscopy.